Differentiability of integrals of real functions with respect to $L_0$-valued measures - Radchenko, V. N. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We obtain conditions for the convergence of expressions $(μ (A))^{ - 1} \smallint _A fdμ$ in $L_0$ as the set $A$ decreases.